Mozambique - Repairing the Ravages of War Initiation Societies and Community Schooling - Mamade, Agostinho (World Bank, Washington, DC, 2012)
Indigenous healing has shown itself to be an effective treatment for the trauma suffered by children in war-torn countries of Africa. Recent experience in Mozambique demonstrates that other dimensions of local culture may be just as important in socially "grounding" a generation of young people uprooted by armed conflict and repairing the ravages of war. By 1990s, community preschools were built to address the growing demand for education. The problems of unattended children remained acute. Then, a new initiative put the community preschools under local control. In the year 2000, the village family created the Association of Friends of the Children of Itoculo, which offers a unique opportunity to couple past and to harness the best of traditional practice in youth initiation to opportunities for viable rural futures in Mozambique. An infusion and selection of indigenous models has proved to be a vital element in the solution to the problems of a war-torn society.